Scale Morphology and Population Differentiation in Exotic Fish Tilapia (Oreochromis mossambicus P. 1852) from Some Major Water Bodies of Western India - Ujjania, N. C.; Sharma, L. L.; Rose, Sanchita; Prajapati, S. D. (International Journal of Bio-resource and Stress Management, 2023)
The study was conducted to find out the morphological variations in tilapia (Oreochrmis mossambicus P. 1852) samples collected from three different water bodies namely Aanasagar lake (S1), Jaisamand lake (S2) and Vallabhsagar dam (S3) during the March 2012 to April 2022 have been studied in the current research. The standard-length and weight ranged between 17.50 to 38.50 cm and 98.50–932.50 g (S1), 15.00 to 24.00 cm and 60.00 to 250.00 g (S2), 15.00 to 33.00 cm and 77.00 to 662.00 g (S3). Key scales were picked out to accomplish the objective of research. The twelve different morpho-parameters (L1, L2,…L12) of Oreochrmis mossambicus P. 1852 scales were measured and analyzed to find presence or absence of morphological variations among the tilapia populations from three habitats. It was found that between these morphometric parameters of Oreochromis mossambicus, L3 and L8 in S1 (0.862), L7 and L12 in S2 (0.830) and L10 and L12 in S3 (0.988) showed very high correlation. Further, the morphological study on measurements was subjected to principal component analysis (PCA) and reported a total 84.98, 89.52 and 93.40 percent of significant variances in scale components (morphometric parameters) for tilapia from S1, S2 and S3 respectively. Variations obtained in morphological (morphometric measurements) data showed four (S1), five (S2) and two (S3) groups of dominant components for the scales of tilapia. It was clearly the formation of disseminated groups in the plot of sheared PCs scores. It is inferred that there was dissimilarity in scale morphological structure of Oreochromis mossambicus collected from different water bodies.